Application of Computational Fluid Dynamics Method for Cross-flow Turbine in Pico Scale - Imam Syofi'i; Dendy Adanta; Aji Putro Prakoso; Dewi Puspita Sari (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Crisis electricity was a crucial issue in the rural area. Crossflow turbine (CFT) in pico in pico scale is the best option for electricity provider for rural areas. Due to its usefulness and development of computer technology, computational fluid dynamics method application for CFT study becomes increasingly frequent. This paper compiles the implementation of the computational fluid dynamic (CFD) approach for CFT on a pico scale. Based on the literature, the Renormalization Group (RNG)  turbulence model is recommended to predict the flow field that occurs in CFT because its error is lower than others turbulence models, the RNG  error of 3.08%, standard  of 3.19%, and transitional SST of 3.10%. Furthermore, six-degrees of freedom (6-DoF) is recommended because it has an error of 3.1% than a moving mesh of 9.5% for the unsteady approach. Thus, based on the review, the RNG  turbulence model and 6-DoF are recommended for the CFT on the pico scale.